STRATEGI BADAN USAHA MILIK DESA DALAM PENGELOLAAN DESA WISATA PAKSEBALI KECAMATAN DAWAN KABUPATEN KLUNGKUNG - Gede Kartika, Ida Ayu; Yudartha, I Putu Dharmanu; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2020)
ABSTRACT This study has purpose to find out and analyze strategies have been used and necessary to be used by village owned business entity in the management of Paksebali Tourism Village, Dawan District, Klungkung Regency. This study has using qualitative descriptive. While informant determining technique used is purposive and snowball sampling. The results of the SWOT Matrix analysis resulted in three alternative SO (Strength-Opportunities) which became the alternative strategy of choice as priority for future strategies such; improve the performance of HR in the management of the Tourism Village as well as in the development of information technology in the marketing process, optimize the development of tourism potential and tourism objects in utilizing the potential of the village as a tourist attraction and increase and develop communication networks and cooperation with the government, villages, managers and stakeholders in the development and management of the Paksebali Tourism Village. Keywords: Village Owned Business Entity, Strategic Planing Process, SWOT Analysis